Asterixis as a Presentation of Cerebellar Ischemic Stroke - Antonio Siniscalchi; Luca Gallelli; Olindo Di Benedetto; Giovambattista De Sarro (Western Journal of Emergency Medicine, 2012)
Asterixis is not yet considered a common neurological sign of cerebellum infarction, and the pathogenic mechanism for asterixis remains elusive. We report a 58-year-old male with moderate hypertension who presented to our emergency department for acute headache in both cervical and occipital regions of the left side. About 2 hours later the patient developed ipsilateral asterixis in the upper left limb; 3 days later the asterixis disappeared. Magnetic resonance imaging of the brain disclosed cerebellarinfarctions at the left superior cerebellar artery. In conclusion, we observed that a transitory asterixis associated with ipsilateral headache can be an initial clinical manifestation of ipsilateral cerebellar infarctions in the superior cerebellar artery area.